The Role of Psychological Distance in Influencing Pro-environmental Behavior Spread: Perceived Justice Enforceability as a Moderator - Xu, Zhengquan; Cao, Qinren; Li, Shuang (Frontiers in Psychology, 2020)
The social system can spread tightly coupled complex practices under the context that members of the social system do not have the shared experience that enables them to coordinate within longstanding tight formal organizations. To promote the understanding of such a process, and given the possibility for other members in the social system to cheat and adopt pro-environment behavior, we draw on the organizational justice literature and the perspective of justice enforceability, and construal level theory, to develop a conceptual model in which the impact of social members’ perceived psychological distance on their response to other social members adoption of pro-environmental behaviors (PEBs) is contingent on their perception of justice enforceability and cognitive appraisals (positive, not significant) towards other social members’ adoption of PEBs. We find that when social members perceive that the adoption of pro-environment behaviors is justice-enforceable, their cognitive appraisals of other social members’ adoption of PEBs is high, and then the more proximal the psychological distance they perceive, the stronger they will react to other social members’ adoption of PEBs. Further, they will adopt and enact such behaviors, otherwise, they would be unwilling to adopt and enact such behaviors. So, uneven perceived psychological distance of social members can harm their adoption and the spread of pro-environment behavior. We tested our model in a survey study. Results show that the proposed model is supported, and our understanding is enhanced about how social members’ willingness to adopt and spread pro-environment behavior is contingent on their perceptions of justice enforceability. This paper is comprised of five parts, of which include an introduction, a part on the theory and hypothesis, data and methods, results and discussion, and conclusion.